Determination of constitutive parameters from a Taylor test using inverse analysis - Maranon, Alejandro; Hernández Acevedo, Camilo (SAGE Publications Ltd, 2017)
Identification of material constitutive parameters is critical for accurate representation of the mechanical behavior of materials at high strain rates. However, customary characterization procedures based on curve fitting of stress-strain curves, in some cases, are not accurate when the mechanical response exhibits strain rate dependency. In this paper, an inverse characterization technique based on the Taylor impact test is proposed. The technique uses a data reduction operator based on line moments and genetic algorithm optimization to determine the optimum constitutive parameters. Material parameters for a low carbon steel associated with the Plastic Kinematic model were determined using the proposed method.

La identificación de los parámetros constitutivos del material es fundamental para representar con precisión el comportamiento mecánico de los materiales a altas velocidades de deformación. Sin embargo, los procedimientos habituales de caracterización basados en el ajuste de curvas de tensión-deformación, en algunos casos, no son precisos cuando la respuesta mecánica presenta dependencia de la velocidad de deformación. En este trabajo se propone una técnica de caracterización inversa basada en el ensayo de impacto de Taylor. La técnica utiliza un operador de reducción de datos basado en momentos de línea y la optimización mediante algoritmos genéticos para determinar los parámetros constitutivos óptimos. Mediante el método propuesto se determinaron los parámetros del material para un acero de bajo carbono asociados al modelo cinemático plástico.
Keywords: Análisis inverso; Acero - Hierro; Inverse analysis; Parameter identification; Steel AISI 1018; Taylor test; Análisis inverso; Identificación de parámetros; Acero AISI 1018; Ensayo de Taylor